ERS International Congress 2021: highlights from the Epidemiology and Environment Assembly. Issue 2 (23rd May 2022) - Bosch de Basea, Magda; Belachew, Abate Bekele; Jankowski, Mateusz; Meteran, Howraman; Dumas, Orianne
In this article, early career members of the Epidemiology and Environment Assembly of the European Respiratory Society (ERS) summarise a selection of four sessions from the Society's 2021 virtual congress. The topics covered focus on chronic respiratory disease epidemiology, the health effects of tobacco and nicotine, and the respiratory health impact of environmental exposures and climate change. While the burden of chronic respiratory diseases such as COPD is expected to increase in the next decades, research on modifiable risk factors remains key. The tobacco and nicotine research presented here focuses on recent evolutions in cigarette alternatives, including vaping and the use of heated tobacco products, and changes in behaviours related to the coronavirus disease 2019 pandemic. The 2021 World Health Organization air quality guidelines were also a major topic of the congress. Despite their benefits, challenges remain in driving and implementing environmental health policies to take into account the respiratory effects observed at very low air pollution concentrations, as well as the impact of climate change on environmental exposures. Highlights of #ERSCongress 2021 from the Epidemiology and Environment Assembly https://bit.ly/3HjLuN3